Ultrastretchable Fiber Sensor with High Sensitivity in Whole Workable Range for Wearable Electronics and Implantable Medicine. Issue 9 (23rd July 2018) - Li, Lianhui; Xiang, Hongyi; Xiong, Yan; Zhao, Hui; Bai, Yuanyuan; Wang, Shuqi; Sun, Fuqin; Hao, Mingming; Liu, Lin; Li, Tie; Peng, Zhenhuan; Xu, Jiaqiang; et al.
Abstract: Fast progress in material science has led to the development of flexible and stretchable wearable sensing electronics. However, mechanical mismatches between the devices and soft human tissue usually impact the sensing performance. An effective way to solve this problem is to develop mechanically superelastic and compatible sensors that have high sensitivity in whole workable strain range. Here, a buckled sheath–core fiber‐based ultrastretchable sensor with enormous stain gauge enhancement is reported. Owing to its unique sheath and buckled microstructure on a multilayered carbon nanotube/thermal plastic elastomer composite, the fiber strain sensor has a large workable strain range (>1135%), fast response time (≈16 ms), high sensitivity (GF of 21.3 at 0–150%, and 34.22 at 200–1135%), and repeatability and stability (20 000 cycles load/unload test). These features endow the sensor with a strong ability to monitor both subtle and large muscle motions of the human body. Moreover, attaching the sensor to a rat tendon as an implantable device allowes quantitative evaluation of tendon injury rehabilitation. Abstract : A buckled sheath–core fiber‐based ultrastretchable fiber sensor is fabricated using a prestretching‐wrapping‐releasing strategy. The fiber strain sensor shows high sensitivity in whole workable strain range (>1135%). These features endow the sensor with a strong ability to monitor subtle muscle motions and large body motions, and a potential possibility for implantable device to quantitatively evaluate tendon injuries.